Proposed pathway for therapeutic drug monitoring and dose escalation of vedolizumab. Issue 5 (24th January 2022) - Nassar, Islam Osama; Cheesbrough, Jonathan; Quraishi, Mohammed Nabil; Sharma, Naveen
Abstract : Vedolizumab is a gut-selective monoclonal antibody approved for the management of Crohn's disease and ulcerative colitis. The available data demonstrate a favourable response to dose escalation in patients with primary non-response or secondary loss of response to vedolizumab. While therapeutic drug monitoring has a proven clinical utility for tumour necrosis factor antagonists, the available guidance for therapeutic drug monitoring and dose escalation of vedolizumab is rather limited. The present review proposes a practical algorithm to use vedolizumab trough levels in the management of treatment failure. Therapeutic drug monitoring can differentiate underexposed patients from those with mechanistic failure. Underdosed patients can respond to dose escalation instead of unnecessarily switching to other treatment modalities. We also review the safety and potential cost-effectiveness of vedolizumab dose escalation, the role of antidrug antibodies and the possible applicability of this strategy to subcutaneous vedolizumab.